EXPLORATION OF ENGLISH SPEAKING ON STUDENT VIDEO ASSIGNMENTS IN SOCIAL MEDIA - Yousef Bani Ahmad (Universitas Singaperbangsa Karawang, 2019)
AbstractThis study aims to determine the mistakes in English pronunciation of students from videos published on social media (Instagram). The video made is the task of the Introduction to Linguistics course, the material presented in the video is the terminology of linguistics taught in classrooms starting from the understanding of linguistics, language, phonetics and phonology, semantics, morposyntax (morpheme, free morpheme, bound morpheme, inflectional, derivational , phoneme, pragmatics, psycholinguistics, and other linguistic material The design of this study uses a descriptive qualitative approach.The samples taken as study participants are second semester students of English language study programs.The sampling technique uses purposive sampling of 6 people.The results of this study indicate that there is a pronunciation error caused by incorrect place and manner of articulation, besides there is a pronunciation error and word suppression in English.The implication obtained in this research is, by knowing the common mistakes that occur in the pronunciation of this language. English and can reduce errors for other English learners.